Maternal Priming of Offspring Immune System in Drosophila. Issue 1 (1st January 2020) - Bozler, Julianna; Kacsoh, Balint Z; Bosco, Giovanni
Abstract: Immune priming occurs when a past infection experience leads to a more effective immune response upon a secondary exposure to the infection or pathogen. In some instances, parents are able to transmit immune priming to their offspring, creating a subsequent generation with a superior immune capability, through processes that are not yet fully understood. Using a parasitoid wasp, which infects larval stages of Drosophila melanogaster, we describe an example of an intergenerational inheritance of immune priming. This phenomenon is anticipatory in nature and does not rely on parental infection, but rather, when adult fruit flies are cohabitated with a parasitic wasp, they produce offspring that are more capable of mounting a successful immune response against a parasitic macro-infection. This increase in offspring survival correlates with a more rapid induction of lamellocytes, a specialized immune cell. RNA-sequencing of the female germline identifies several differentially expressed genes following wasp exposure, including the p eptiodog lycan r ecognition p rotein-LB (PGRP-LB). We find that genetic manipulation of maternal PGRP-LB identifies this gene as a key element in this intergenerational phenotype.